Effektivisering och optimering av lagerytor : En fallstudie vid Smurfit Kappa Kraftliner Piteå - Lundmalm, Therese; Ström, Malin (2011)
When customers’ demand of products increases, it will make companies to produce more and it will force them to expand their inventories. The company’s purpose is to produce customized products. The strive for the company should be to optimize the processes and different activities from supplier to customer. One of the necessary activities in the chain from production to customer is inventory and warehouse management and it should be in the company’s interest to do things right, to have high efficiency and not waste its resources. Smurfit Kappa Kraftliner Piteå, the company which this study has been made at, is one of Europe’s biggest kraftliner mill and producer of kraftliner, a base paper made from fresh fiber. Today the company has many inventories in its supply chain from suppliers to customers; among others at the harbor Haraholmen in Piteå, Sweden. The aim of this study has been to focus on the two warehouses in the harbor. The purpose of this study was to investigate current inventory layout and try to make it more efficient by studying the two inventories’ in- and outflow. Further, the manual handling of incoming orders was examined in order to suggest improvements. To fulfill the purpose of the study, interviews and observations were made at the harbor Haraholmen and at Smurfit Kappa Kraftliner Piteå. Also an automatized summary over incoming orders was programmed. Problems were identified from an analysis of the current situation. These problems were factors that contributed to the aim of this study. Some of these problems were the manual creation of a map of the warehouses and the summary of incoming orders, which contribute to inefficiency. As changes in order are incoming continuously, the map of the inventory has to be modified, which causes more work for the employees than necessary. Something else that was discovered was the fact that one of the two warehouses is smaller than the other. As the company today uses one warehouse per week, the risk of lack of space increases in the smaller one. ...